Online Shopping Behavior of FEB UNDARIS Students in the Perspective of TPB (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
The development of e-commerce and social commerce has driven significant changes in student shopping behaviour, including at FEB UNDARIS. Ease of access, digital promotions, and the influence of social media have led students to shop online more frequently, even impulsively. This study aims to analyse how attitudes, subjective norms, and perceived behavioural control interact in shaping students' online shopping behaviour using the Theory of Planned Behaviour (TPB) framework. This study uses a descriptive qualitative method with in-depth interviews with ten students who actively shop online. The data were analysed to understand the experiences, perceptions, and social factors that influence their decisions in digital transactions. The results show that positive attitudes towards efficiency and promotions, social pressure from friends and influencers, and high perceived behavioural control due to technological convenience work simultaneously to reinforce online shopping intentions and actions. These three TPB components support each other and trigger increasingly impulsive consumption patterns in the digital environment.